2020
DOI: 10.1016/j.gore.2020.100658
|View full text |Cite
|
Sign up to set email alerts
|

Benign ovarian thecoma with markedly elevated serum inhibin B levels mimicking adult granulosa cell tumor

Abstract: Highlights A rare case of markedly elevated inhibin B associated with an ovarian thecoma. Inhibin B lacks specificity as a tumor marker for adult granulosa cell tumor. A full differential for elevated Inhibin B is important for improved preoperative counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Therefore, elevated serum inhibin B is regarded as a classic marker of GCT. However, Carballo et al [ 9 ] demonstrated a case of benign ovarian thecoma with markedly elevated serum inhibin B levels, suggesting that inhibin B is not entirely specific to GCT. Patients with endocrine disorders need their inhibin B levels to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, elevated serum inhibin B is regarded as a classic marker of GCT. However, Carballo et al [ 9 ] demonstrated a case of benign ovarian thecoma with markedly elevated serum inhibin B levels, suggesting that inhibin B is not entirely specific to GCT. Patients with endocrine disorders need their inhibin B levels to be evaluated.…”
Section: Discussionmentioning
confidence: 99%